Livestock and climate change frames and interaction strategies in East Africa: Exploring tensions between adaptation and mitigation options - Cramer, Laura K.; Dewulf, Art; Crane, Todd A. (Informa UK Limited, 2025)
East African livestock systems, which support many livelihoods, are suffering from climate change but also contribute a large portion of national greenhouse gas emissions. There are various ways to frame livestock and climate change problems and solutions. We use data from interviews, policy documents and participant observations of science-policy interfaces in Ethiopia, Kenya and Uganda to answer: (1) How do frames used by scientists and policymakers affect discussions about climate change and livestock keeping in East Africa? and (2) What framing interaction strategies are employed to deal with ambiguity in science-policy interfaces? Findings show emphasis is given to framings describing livestock and climate change problems and less to response framings. While adaptation and mitigation are both used as issue frames in general discussions, funding availability to address climate issues draws attention to the need for measurement, reporting and verification systems, leading to more concrete discussions on mitigation-related response options and less attention on adaptation. Actors use different interactional framing strategies to co-construct meaning around problems and response options. The findings highlight the need for governments and partners to co-create knowledge on how livestock interventions can address adaptation and mitigation simultaneously to move away from the adaptation-mitigation divide in response framings.